LIVESTOCK RECONVERSION: : a possible trajectory for the sustainability of cattle production in Maranhão, Brasil - Mauroni Alves Cangussu; Tiago Cunha Rocha; Diego Carvalho Viana (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
The cattle production systems in Brazil are based on the use of pastures, but due to the seasonality of forages during the drought period, meat production is significantly reduced. Livestock in Maranhão has low productivity when compared to other states, with the level of adoption of insufficient and ineffective technologies, generating instability in the supply of meat and its products and in the income of producers. The introduction of more ecological and sustainable management has been increasingly used to optimize meat production without promoting degradation of the area, within the methodologies the Silvipastoral System (SSP) stands out for reducing expenses with fertilizers, favors the performance of animals by reducing the thermal stress caused by high temperatures and promotes greater income to the producer for presenting higher revenues from the sale of animals and trees.